2022
DOI: 10.36149/0390-5276-261
|View full text |Cite
|
Sign up to set email alerts
|

Acute peri-prosthetic joint infection: improving diagnosis through the novel alpha-defensins test

Abstract: Background. The matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has recently been proposed as novel alpha-defensins test for diagnosis of peri-prosthetic joint infections (PJIs). The aim of the current study is to assess the diagnostic accuracy of alpha-defensins MALDI-TOF MS in case of acute PJIs. Methods. This prospective study included a series of 10 consecutive patients affected by PJIs according to the 2018 MSIS criteria. Synovial fluids were assessed for routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Analysis of synovial fluids represents an important tool for diagnosis of bone and joint infections, including prosthetic ones, since it can contribute to optimize patient management before surgery. In the recent past, it has been widely demonstrated that measurement of inflammatory markers in synovial fluids is a more specific approach than their evaluation in blood [22][23][24]. Nonetheless, culture remains crucial for the diagnosis of osteo-articular infections and particularly of PJI [25].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of synovial fluids represents an important tool for diagnosis of bone and joint infections, including prosthetic ones, since it can contribute to optimize patient management before surgery. In the recent past, it has been widely demonstrated that measurement of inflammatory markers in synovial fluids is a more specific approach than their evaluation in blood [22][23][24]. Nonetheless, culture remains crucial for the diagnosis of osteo-articular infections and particularly of PJI [25].…”
Section: Discussionmentioning
confidence: 99%